ROPADAS (ROBOT PRAMUSAJI CERDAS) BERBASIS LINE FOLLOWER SYSTEM - Mulyana, Ardiyan Rofiq; Yahya, Luthfi; Khoirunnisa, Rilla; Tamara, Claricha Audi (Program Kreativitas Mahasiswa - Teknologi, 2013)
Often times, the waiter exhausted, tired and bored in their duties and lead to faulty work. Robots that will be made is a mobile robot that is based intelligent robot line follower waitresses who will follow the specified trajectory line towards the customer tables ordering food.Making intelligent robot waiter consists of 3 stages. First, hardware, software and mechanics design. Secondly, manufacturing system consisting of electronic, mechanical design and system programming. Third, troubleshooting and refinement tool to make sure tools can work well. This robot will follow the black track line from kitchen to the dining tables of customers.